New Religions and State's Response to Religious Diversification in Contemporary Vietnam : Tensions from the Reinvention of the Sacred - Hoang, Chung Van (Springer International Publishing : Imprint: Springer, 2017)
This book approaches newly emerging religious groups through the interplay between religious and non-religious spheres and in the context of religious diversification in post-Renovation Vietnam. It considers the new religious groups as a part of religious reconfiguration in contemporary Vietnam caused by intensified interactions among these spheres. It explores changes of relationship between religions, and changes between the religious sphere and the political, economic and public spheres. Specifically, it traces trajectories of religious development in relation to politico-economic changes in this rapidly modernising nation. The book tests a hypothesis that at least some new yet unrecognized new religious groups have a positive/ active role in modernisation rather than a negative/reactive role. To this end, the book draws on a number of research approaches and methodologies in an effort to provide readers with a multi-faceted understanding of Vietnam's new religious groups, including how the current socialist state has responded to their emergence and challenges. The research is interdisciplinary in orientation, drawing on sociology and anthropology. It is also comparative in that it bases its argument on a consideration of three distinct new religious groups in Vietnam. The research is also qualitative and ethnographic in that it drew on some of the techniques associated with participant observation during a sustained period of fieldwork amongst the targeted groups. The concept of religious reconfiguration developed in this book provides a framework for the study of religion in Vietnam which opens the way to further analysis from a comparative perspective. Meanwhile, an emphasis upon religious reinvention which addresses processes of remaking, transforming, legitimating and accommodating can be useful for research into New Religious Movements elsewhere in Asia. A research in the challenges of new religions through could act as a catalyst for interdisciplinary studies based on detailed empirical study of religious diversity and of religious freedom by other scholars. It is hoped that this research might help to give a voice to religious minorities that are often the victim of stereotyping, misunderstanding, and punitive treatment. The book is suitable for post-graduate students and social researchers who are interested in religious revival, religious diversification, state-religion relationships, and state's regulation of new religions.
Keywords: Social sciences.; Religion and sociology.; Ethnology -- Asia.; elektronické knihy; electronic books